Salvage Therapies for Autoimmune Hepatitis: A Critical Review - Roberts, Stuart K.; Kemp, William (Seminars in Liver Disease, 2017)
Several salvage therapies have been identified for autoimmune hepatitis refractory or recalcitrant to conventional therapy; however, the optimal salvage strategy remains unclear. High-dose prednisolone is currently recommended as the front-line salvage therapy, with alternative immunosuppressive therapies reserved for continuing treatment failure. Of the second-line therapies, the calcineurin inhibitors, cyclosporine and tacrolimus, and mycophenolate mofetil are preferred and have the most accrued clinical data. However, none of these have undergone rigorous clinical evaluation via randomized clinical trials. Tacrolimus is generally preferred over cyclosporine because of its higher potency and increased utility in organ transplantation. Mycophenolate is particularly useful for azathioprine intolerance but also for nonresponse to standard treatment. Subjects with progressive liver failure should undergo liver transplantation evaluation. The appropriate timing, dosing, and monitoring of salvage therapies require determination. Several promising immunosuppressive therapies have been developed for autoimmune diseases including molecular agents that may enhance regulatory T cell activity and function.
Keywords: autoimmune hepatitis; cyclosporine; tacrolimus; mycophenolate